Methotrexate for the Treatment of Thyroid Eye Disease - Diego Strianese; Adriana Iuliano; Mariantonia Ferrara; Chiara Comune; Immacolata Baronissi; Pasquale Napolitano; Alessia D’Alessandro; Piergiacomo Grassi; Giulio Bonavolontà; Paola Bonavolontà; Antonio Sinisi; Fausto Tranfa (Journal of Ophthalmology, 2014)
Background/Aim. To evaluate the efficacy of methotrexate for the treatment of thyroid eye disease (TED). Methods. 36 consecutive patients with active TED, previously treated with corticosteroids but stopped due to the occurrence of side effects, were commenced on methotrexate therapy. Two different weekly doses were administered depending on the weight of the patient (7.5 mg or 10 mg). Clinical activity score (7-CAS), visual acuity (VA), ocular motility, exophthalmos, and eyelid position were retrospectively evaluated at 3, 6, and 12 months and compared with baseline data. Results. There was a statistically significant improvement in 7-CAS at 3, 6, and 12 months after treatment (P<0.0001). There was no significant change in visual acuity. Ocular motility disturbances improved at 6 and 12 months (P<0.001). There was no significant change in exophthalmos (mean 24 mm, SD 3 mm) or eyelid position (marginal reflex distance mean 6 mm, SD 1.5 mm) during the follow-up period. No side effects were registered. Conclusions. Methotrexate therapy is effective in reducing CAS and ocular motility disturbances. No significant improvement in proptosis or eyelid retraction should be expected from this treatment. Eventually, it might be considered a suitable alternative treatment in TED for patients who cannot tolerate steroids.